Bioactive ROS‐scavenging nanozymes for regenerative medicine: Reestablishing the antioxidant firewall. Issue 3 (27th July 2020) - Wu, Haibin; Liao, Hongwei; Li, Fangyuan; Lee, Jiyoung; Hu, Pingjing; Shao, Wei; Li, Xiangzi; Ling, Daishun
Abstract: Bio‐therapeutics, such as stem cells, nucleic acids, and growth factors, represent the frontier of regenerative medicines. The excessive accumulation of reactive oxygen species (ROS) is an essential mechanism in tissue degeneration or injury, which stimulates deleterious oxidative damage to the administered bio‐therapeutics. Likewise, a high level of ROS provokes critical damage to vital endogenous biomacromolecules, such as proteins, lipids, and nucleic acids, which restricts the innate regeneration. Recently, ROS‐scavenging nanozymes gain increasing attention from the field of regenerative medicine, which are able to protect bio‐therapeutics and endogenous actives from oxidative damage and facilitate innate regeneration. ROS‐scavenging nanozyme becomes a novel bioactive platform technology that enables the development of tailored materials for regenerative therapies. Herein, we provide a review on the chemical mechanism of ROS‐scavenging nanozymes, and summarize their applications within the scope of tissue repair and regeneration. We also discuss the current limitations and future directions of ROS‐scavenging nanozymes in the field of regenerative medicine from a perspective of clinical translation. Hopefully, our work may inspire further innovation of advanced ROS‐modulating biomaterials, which will accelerate the evolution of regenerative medicine. Abstract : ROS‐scavenging nanozyme represents a novel bioactive platform that can protect bio‐therapeutics from oxidative damage and facilitate the innate regeneration, which holds tremendous promise to accelerate the evolution of regenerative medicine. Herein, the progress of ROS‐scavenging nanozymes in the field of regenerative medicine is reviewed. The current limitations and future directions of ROS‐scavenging nanozyme‐based regenerative medicines are discussed.